Church Communications Highlights 2017 - Francis X. Rocca; John P. Wauck (Church, Communication and Culture, 2018)
Every year, there are thousands of Vatican-related news stories, and Pope Francis, in particular, has generated non-stop media attention. In this regard, the year 2017 was no different than the previous three years of this pontificate. Amid such a vast quantity of coverage, it can be difficult to pinpoint the truly salient stories, the ones that, in the long run, are going to make a difference for the Church and for culture. In order to sort through the reportage and find our bearings, we decided to ask a veteran reporter to comment on what he considers the most important stories of 2017. Francis X. Rocca has been The Wall Street Journal’s Vatican correspondent since 2015, and before that he was the Rome bureau chief of Catholic News Service, the news agency of the U.S. Conference of Catholic Bishops, for three years. Our conversation took place on 14 December 2017 in Rome. The following transcript has been edited for clarity.